Double the fun: Mars scientists push NASA to send rock-harvesting rover to two sites. (25th October 2018) - Witze, Alexandra
The US$2.4-billion mission aims to collect the first samples for return from the red planet. Mars scientists push NASA to send rock-harvesting rover to two sites The US$2.4-billion mission aims to collect the first samples for return from the red planet.